Analysis of the Impact of Selected Anesthetic Agents on Neurobehavioral State of a Newborn - Dorota Pilch; Jacek Rudnicki; Krzysztof Safranow; Elżbieta Grochans (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. An increasing percentage of children are born through C-sections. Both mother and child are exposed to potential obstetric, anesthesia and neonatal complications. Hypoxia associated with obstetric or anesthetic complications can lead to fetal hypoxia, and induce adaptation difficulties in the postpartum period or permanent developmental disorders. Knowledge of issues related to the perioperative care of the mother and child will minimize complications and provide high-quality care. Aim. The aim of the study was to analyze the impact of opioids in analgesia and hypotension during C-section on neonatal neurobehavioral state. Material and Methods. The study involved 102 mothers and their babies born by C-section. The study was approved by the Bioethics Committee of PUM. The inclusion criterion was the lack of systemic diseases in the mother and the gestational age over 36 weeks. All mothers were subarachnoidally anesthetized for the labor. Newborns after two days of life were assessed by NBAS (Neonatal Behavioral Assessment Scale). Results. Neonatal reflexes in the study group were normal. Newborns of mothers who were added fentanyl to anesthesia, did not differ in behavior from the others (p>0.05). After adding Morphini Sulfas 0.1% Spinal to anesthesia there were observed statistically significant differences in the behavior of newborns, compared to infants whose mothers did not receive it, in terms of sound stimulus habituation (p=0.04) in favor of those whose mothers received MF Spinal intrathecally. Children of mothers anaesthetized without the addition of MF Spinal presented higher self-calming abilities than the others (p=0.03). The ability of calming down differed infants of mothers whose blood pressure declined during anesthesia (p=0.04). Conclusions. Subarachnoid anesthesia with opioid supplementation for C-section as well as an anesthesia-related decrease in blood pressure slightly affected neurobehavioral state of infants born by C-section comparing to those whose mothers had not received opioids intraspinally and had not experienced a blood pressure decrease. (JNNN 2016;5(3):92–98)